Rotary Cutting Tool With Anti-Rotation Feature - KEVIN GAMBLE; JAMES WAGGLE (2016)
A rotary cutting tool, such as a slotting cutter, includes a cutter body rotatable in a predetermined direction on a central axis perpendicular to a plane of the cutter body. A plurality of cutting insert-receiving pockets are formed at predetermined locations about the cutter body. A cantilevered member can be integrally formed in the cutter body or attached to the cutter body as a separate component. A tip of the cantilevered member at least partially extends into each insert-receiving pocket such that the cantilevered member exerts a biasing force against a cutting insert at a location so as to counteract a tendency of the cutting insert to rotate within the insert-receiving pocket during a cutting operation. 种回转刀具，例如种槽铣刀，包括个可围绕垂直于所述刀体平面的中轴按预定方向旋转的盘状刀体。在绕所述刀体的预定位置上形成多个切削刀片收纳槽。悬臂式构件可集成于所述刀体中，或者作为个独立的组件安装到所述刀体上。所述悬臂式构件的尖端至少部分伸入每个刀片收纳槽，以至于所述悬臂式构件在切削刀片的某个位置上形成偏置力，抵消掉切削作业期间所述刀片在所述刀片收纳槽内旋转的趋势。